Pengaruh Work-Life Balance, Kecerdasan Emosional, dan Personal Value terhadap Kinerja Pegawai Non Medis Rumah Sakit Khusus Jiwa (RSKJ) Soeparpto Provinsi Bengkulu - Putri, Annisa; Army, M. Noor; Fauzan, Fauzan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the influence of work-life balance, emotional intelligence, and personal values on the performance of non-medical employees at the Soeprapto Mental Hospital (RSKJ) in Bengkulu Province, both partially and simultaneously. The research employed a quantitative approach using multiple linear regression analyses processed through SPSS version 27. The results show that, partially, all three independent variables significantly affect employee performance. Work-life balance has the most dominant influence, with a regression coefficient of 0.378 and a significance value of 0.002, followed by emotional intelligence (coefficient = 0.317; p = 0.010) and personal values (coefficient = 0.197; p = 0.022). Simultaneously, these variables also significantly impact employee performance, with an F value of 21.448 and a significance level of p < 0.001. These findings indicate that employee performance is not solely determined by technical skills but is also strongly influenced by life balance, emotional regulation, and personal values. Therefore, it is recommended that RSKJ Soeprapto’s management develop a human resource strategy that supports emotional well-being, fosters positive work values, and facilitates a healthy work-life balance among employees.